Why a new journal?. Issue 1 (1st January 2016) - Arasa, Daniel
Abstract : Mission statement: Church, Communication and Culture (CC&C) is an open access academic journal of the Pontifical University of the Holy Cross' School of Church Communications. Published by Taylor & Francis (Routledge), the Journal is dedicated to deepening knowledge and understanding about the dialogue between religion, communication and culture in the public arena. Based on comprehensive data analysis and theoretical inquiry, it offers an international forum where researchers and practitioners can advance quality communication research on the Catholic Church and other religious communities.